The effects of Tenidap on cytokine induced proliferation of human synovial fibroblasts in vitro. Issue 4 (April 1994) - Mattey, D L; Evans, E; Dawes, P T
Abstract : OBJECTIVES–Tenidap, a new anti-rheumatic agent, is a lipoxygenase and cyclooxygenase inhibitor, and is reported to inhibit the production and action of interleukin 1 (IL-1). Since eicosanoids, IL-1, and other cytokines may influence the growth of fibroblasts in the joint synovium the study was carried out to determine the effects of Tenidap on cytokine induced proliferation of these cells in vitro. METHODS–Cell cultures derived from patients with a variety of rheumatic diseases were cultured in different concentrations of Tenidap sodium, with or without IL-1, tumour necrosis factor alpha (TNF), IL-6, basic fibroblast growth factor (bFGF), or transforming growth factor beta (TGF beta). Cell proliferation was measured using a crystal violet colourimetric assay. Prostaglandin E2 levels in culture supernatants were measured by radioimmunoassay. RESULTS–Tenidap at concentrations above 10 micrograms/ml inhibited cell growth, while at 1.25-5 micrograms/ml there was a small but significant increase in proliferation compared with controls. A further increase in growth was obtained when cells were incubated with Tenidap+IL-1, TNF or bFGF, and this was significantly higher than in the presence of any cytokine alone. Stimulation of IL-1 induced growth by Tenidap was reduced by addition of high levels of exogenous PGE2 (100 ng/ml) although growth was still higher than in IL-1 alone. CONCLUSIONS–Depending on concentration, Tenidap may inhibit or stimulate synovial fibroblast growth. Our results suggest that augmentation of growth by low concentrations cannot be explained by inhibition of PGE2 production alone. Tenidap may directly stimulate cell growth or may block other fibroblast factors which are involved in control of cytokine induced proliferation.